Analisis Alternatif Penyelesaian Sengketa Antara Pihak Nasabah dengan Industri Jasa Keuangan pada Era Otoritas Jasa Keuangan (OJK) - Lukmanul Hakim (KEADILAN PROGRESIF, 2015)
Banking is one of the institutions that have an important and strategic role in various fields, among others in community activities, especially in the field of financial and economic activities to meet the needs of any particular individual. The continued development of the banking business is currently pushing the more the likelihood of disputes between bank customers and banks which could reduce public confidence in the Bank. As from January 2014 the functions, duties and powers of regulation and supervision of banking mediation activities previously carried out by Bank Indonesia (BI), which has now been transferred to the Financial Services Authority (FSA). Then, after the FSA has a role in dispute resolution, including out of court dispute resolution conducted by the FSA through the Institute of Alternative Dispute Resolution (LAPS).